(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
In the normal as well as in the oxygen deficiency conditions research has been made to study the influence of CA1 area of hippocampus on impulse activity of respiratory neurons of medulla oblongata. In conditions of normal atmospheric pressure the electrical stimulation of CA1 area has had mainly inhibiting influence. In the initial phase, on 4–5 thousand meter altitude, activation of frequent discharge of neurons occurred. In this situation the inhibiting influence of stimulation of CA1 area of hippocampus was more accentuated than in conditions of normoxia. In the second phase, 7.5–8 thousand meters on the reduction of the impulse activity of neurons, stimulation of CA1 area induced uncharacteristic reactions of those neurons.